O realismo experimental como resposta plausível à descontinuidade da ciência - Tiago Luis Teixeira de Oliveira (2017)
This present thesis discusses the possibility of a scientific realism capable of facing the anti-realistic challenge of pessimistic meta-induction. We try to depict the formulated pessimistic meta-induction such as a relevant challenge that any scientific realism must take into account the possibility that present theories (and their ontology) suffer the same fate of theories of the past (whose theoretical terms were considered non-referential). In sequence we argue that the experimental realism initially proposed by Hacking (1983) and Cartwright (1983) may be consistent with the pessimistic meta-induction, either because the abandoned theoretical entities through the history of science did not meet the requirements of that type of realism, or because a theoretical change does not seem to threaten unobservable entities experimentally manipulated. We also analyze the merits and the weaknesses of the criticism directed to experimental realism. We assume that an epistemical interpretation by Suárez (2008) and new formulations inspired on experimental realism (such as Chakravartty, 2007 and Egg, 2012) overcome the criticism to which the Hackings and Cartwrights realism was subjected. We argue that these reformulations can keep the advantage of experimental realism already highlighted in this study, namely the ability to offer a realistic criterion compatible with pessimistic meta-induction.